Pemanfaatan Tumbuhan Hutan sebagai Bahan Pengobatan Tradisional oleh Masyarakat Suku Dayak Meratus Kalimantan Selatan - Kissinger, Kissinger; Abdullah, Abdullah; Fitria, Abdi; P., Rina M.N. (Proceedings Series on Physical & Formal Sciences, 2021)
The use of forest plants as medicinal materials is an essential part of the life of indigenous peoples, one of which is the Dayak tribe of the Meratus Mountains. This study aimed to analyze the use of plants as medicinal ingredients for the indigenous Cabai community in Patikalain Village, Hantakan District, Hulu Sungai Tengah Regency, which is part of the Meratus Mountains Dayak tribe. The method of data collection was done by semi-structured interviews. Selected respondents were determined by purposive sampling and snowball sampling techniques. Data were analyzed by tabulation matrix. There were 18 types of forest plants that were used as medicine by the indigenous people of Cabai. The most widely used plant habitats for medicinal purposes were shrubs/shrubs and trees. Roots and leaves were the most widely used plant parts in medicine. There were at least 23 diseases that could be treated with various types of plants. Forest plants were widely used for internal medicine compared to external medicine. Treatment using plant ingredients was the first alternative used by the community in medicine. If this did not work, then community members who were sick would be directed to seek treatment at the Local Health Care Unit. If modern medicine did not work, the next alternative, then additional treatment using traditional rituals, was the last option. This finding was a contribution to knowledge in the traditional medicine system of the local community.